2001
DOI: 10.1677/joe.0.1690321
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of progesterone, follicle stimulating hormone and glucocorticoids in survival of serum-free cultured granulosa cell explants

Abstract: To investigate the role of progesterone (P4) as a survival factor in quail granulosa cell explants, P4 content was determined under various conditions and correlated with apoptotic indexes (AIs) evaluated by 2 ,6 -diamidino-2-phenylindole (DAPI)-staining. Analysis of serum-free cultures from 24 to 96 h shows decreased P4 levels in the medium paralleled by increasing AI. Inhibiting apoptosis by gonadotropic support (FSH, 100 ng/ml) stimulates a 3-fold increase of the P4 level in the medium (83·49 8·69 vs 26·31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
1
7
0
2
Order By: Relevance
“…Gonadotrophins can induce the expression of pro-survival molecules, including bcl-2, GATA-4, FLIP and XIAP, and decrease the expression of proapoptotic molecules, such Bax, Apaf1, Fas/FasL and p53 [112,132,134]. It has been shown that FSH can mediate both progesterone-dependent and progesterone-independent survival pathways in pre-ovulatory avian GCs [135].…”
Section: Gonadotropins and Intraovarian Regulatorsmentioning
confidence: 99%
“…Gonadotrophins can induce the expression of pro-survival molecules, including bcl-2, GATA-4, FLIP and XIAP, and decrease the expression of proapoptotic molecules, such Bax, Apaf1, Fas/FasL and p53 [112,132,134]. It has been shown that FSH can mediate both progesterone-dependent and progesterone-independent survival pathways in pre-ovulatory avian GCs [135].…”
Section: Gonadotropins and Intraovarian Regulatorsmentioning
confidence: 99%
“…Progesterone treatment increases granulosa cell survival in quail (22), cow (23,24), rat (18,20,25), and primates (21), including humans (19), yet the mechanism of progesterone's antiapoptotic action remains unclear. Although this progestin action has been attributed to the presence of PR in some cell models (22)(23)(24)(25), it has also been demonstrated in cells that lack PR activity (18 -21).…”
mentioning
confidence: 99%
“…Overexpression of p53 results in granulosa cell apoptosis Kim et al, 1999;Hughes and Gorospe, 1991;Wang et al, 2002;Mussche and D'Herde, 2001;Orisaka et al, 2006;Zwain and Amato, 2001). …”
Section: Gonadotropinsmentioning
confidence: 99%